1993
DOI: 10.1152/ajpheart.1993.265.4.h1132
|View full text |Cite
|
Sign up to set email alerts
|

Role of adrenergic tone in mechanical and functional properties of carotid artery during aging

Abstract: The present study was designed to assess the role of the adrenergic tone in the regulation of carotid arterial compliance during aging. An experimental model of in situ isolated carotid arteries has been used to evaluate the elastic properties of the arterial wall in young (3-mo-old) and older (18-mo-old) Wistar rats. Binding experiments were performed in the same strain of rats to evaluate alpha 1- and beta-adrenoceptor affinity and density. In a third set of experiments, structural parameter of the carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Our results are in agreement with those of clinical and experimental studies: the arterial wall progressively thickens and becomes stiffer with age [17][18][19][20]. The present study confirms an increase in collagen content in the arterial wall of aorta of old rats [15].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with those of clinical and experimental studies: the arterial wall progressively thickens and becomes stiffer with age [17][18][19][20]. The present study confirms an increase in collagen content in the arterial wall of aorta of old rats [15].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is unlikely that the time-dependent reduction in methoxamine-induced tonic vasoconstriction in 8-week-old preparations is due to decreased constrictive activity of arterial smooth muscles. Some studies have shown no age-dependent changes in the density of α 1 -adrenoceptors (22,23). Furthermore, high KCl-induced vasoconstriction was not altered with aging, suggesting that membrane depolarization-induced smooth muscle contractility is not responsible for the age-related disappearance of the time-dependent reduction in methoxamine-induced vasoconstriction.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacologically induced increases in adrenergic tone have been shown to decrease distensibility of in situ isolated carotid arteries in rats (3). Conversely, carotid and femoral arterial distensibility increased and elastic modulus (ie, stiffness) decreased in sympathectomized rats (4).…”
Section: Introductionmentioning
confidence: 99%